AKUMULASI TIMBAL (Pb ) PADA TALUS LICHENES DI KOTA PEKAN BARU - Nursal '; Firdaus '; basori ' (Biogenesis, 2005)
The  research  accumulation  of Leads in Lichens  thallus  had  carried  out  on  March  until  June 2003.  Samples o f   Lichenes   was   taken   from   tree   bark   at   three   locations   in   Pekanbaru   City ,   were;   Sudirman   and Soebrantas  streets.   The  accumulation  of  Leads  analyze  with  Atomic  Absorbance  Spectrophotometers - AAS .  The  results of this research  that  Lead  contents  in Lichenes that  grow  on  tree  bark on  Pekanbaru City about    4,36 - 23,14  ppm.  The  correlation  of relative  humidity  of air  with  Lead  accumulation  in  Lichenes  thallus had  more higher  than another  factors .   Key words : Leads, Lichenes, Pekanbaru city